2017
DOI: 10.1021/acs.chemmater.6b05392
|View full text |Cite
|
Sign up to set email alerts
|

Modification of Nanoporous Silicon Nitride with Stable and Functional Organic Monolayers

Abstract: This study describes the formation of functional organic monolayers on thin, nanoporous silicon nitride membranes. We demonstrate that the vapor-phase carbene insertion into the surface C–H bonds can be used to form sub-5 nm molecular coatings on nanoporous materials, which can be further modified with monolayers of polyethylene glycol (PEG) molecules. We investigate composition, thickness, and stability of the functionalized monolayers and the changes in the membrane permeability and pore size distribution. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 55 publications
2
11
0
Order By: Relevance
“…We hypothesized that PEG‐coating would improve discrimination and possibly block albumin transmission completely. We previously showed that NPN functionalization with PEG1000 created a conformal ≈7 nm coating, which shrank pores by ≈14 nm in sieving tests . Because our sieving curves for 75 nm NPN‐O begin to show hindrance of solute transport at ≈20 nm, we reasoned that PEG‐coating would significantly hinder the transport of molecules starting at ≈6 nm, which is roughly the hydrodynamic diameter of albumin but >1.5 times larger than the hydrodynamic diameter of cytochrome c (3.6 nm) .…”
Section: Resultsmentioning
confidence: 91%
See 3 more Smart Citations
“…We hypothesized that PEG‐coating would improve discrimination and possibly block albumin transmission completely. We previously showed that NPN functionalization with PEG1000 created a conformal ≈7 nm coating, which shrank pores by ≈14 nm in sieving tests . Because our sieving curves for 75 nm NPN‐O begin to show hindrance of solute transport at ≈20 nm, we reasoned that PEG‐coating would significantly hinder the transport of molecules starting at ≈6 nm, which is roughly the hydrodynamic diameter of albumin but >1.5 times larger than the hydrodynamic diameter of cytochrome c (3.6 nm) .…”
Section: Resultsmentioning
confidence: 91%
“…Paired t ‐tests ( n = 3) determined there was no significant difference ( p > 0.05) between urea fractional losses at 3, 4, and 5 h and one‐way analysis of variance (ANOVA) showed there was no significant difference ( p > 0.05) between PEG and non‐PEG membranes regarding urea clearance. This result suggests that while native NPN‐O likely adsorbs some protein from the solution, this does not hinder small molecule passage. This result is also in agreement with a 23% reduction predicted by a computational model of the system at these flow rates (Figure b; see Supporting Information).…”
Section: Resultsmentioning
confidence: 91%
See 2 more Smart Citations
“…pore size, porosity, membrane thickness). The presence of protein adsorption and platelet activation, even though less than the positive control, points to the need for more careful design of the fluid flow in future experiments, as well as the need for surface functionalization, which our group has developed for nitride surfaces [19]. …”
Section: Discussionmentioning
confidence: 99%